A Semantic Web system for supporting teachers using ontology alignment. (10th September 2007) - Kasai, Toshinobu; Yamaguchi, Haruhisa; Nagano, Kazuo; Mizoguchi, Riichiro
In Japan, it is important to provide teachers of Information Technology Education (IT) with a powerful help system that can locate and provide access to a variety of useful information resources. To this end, we built an ontology of the goal of IT education and its applications based on Semantic Web technology. This application was based on the alignment of ontologies to reuse the results of other research. Furthermore, we propose a Goal Transition Model to show a skeleton of the transition of instructional goals based on ontologies. Finally, we propose support functions that are used in the model.